A novel method to detect meat adulteration by recombinase polymerase amplification and SYBR green I. (15th November 2018) - Cao, Yuhao; Zheng, Kaizhi; Jiang, Junfang; Wu, Jianliang; Shi, Fangxiong; Song, Xuemei; Jiang, Yongqing
Highlights: RPA identified meat sources sensitively and specifically. RPA took only 30 min at 37 °C. SYBR green I caused chromism reaction with RPA amplicons. RPA and SYBR green I detected 1% pork adulteration in beef and mutton. RPA and SYBR green I was simple, easy and time-saving. Abstract: Meat adulteration is one of the most common economic fraudulences in food industry. Current methodologies of meat source identification are complex, time-consuming and require sophisticated equipment. Hence, a simpler species specific method to determinate species is urgently needed. Here, we developed a novel method to visually identify the adulteration of meat using recombinase polymerase amplification (RPA) and SYBR green I (SG). At the isothermal temperature of 37 °C, RPA specifically identifies duck, chicken, cow, sheep and pig within 30 min of water bath. The RPA amplicons were successfully visualized by adding SG I. Furthermore, RPA can differentiate species of boiled, microwaved, high pressured or fried samples. Finally, using this system, we visually identified 1% pork adulterated in mutton or beef.